Temperature effects on the metabolism of amphibians and reptiles: Caveats and recommendations - de Andrade, Denis Vieira [UNESP] (Taylor & Francis, 2017)
Introduction All animals need energy. Indeed, each and every activity, or behavior, an animal will engage in throughout its lifetime will require the use of energy. As in the majority of other animals, Squamate reptiles derive their energy from the breakdown of organic substrates, often referred to as catabolism, acquired through feeding. Adenosine triphosphate (ATP) will eventually be hydrolyzed to adenosine diphosphate (ADP) and Pi, releasing the energy stored in its chemical bonds to power subcellular structures, cells, tissues, organs, and systems, which, acting under neural and/or humoral control, will be manifested as identifiable activities and behaviors (see Chapter 1). Thus, by focusing on metabolism, one is in a privileged position to appreciate the interactions of a given organism in terms of energy exchange with the biotic and abiotic components of its particular environment. This is of indisputable value as it can reveal current and future tradeoffs in terms of functional and energetic constraints with important ecological and evolutionary consequences (see Bennett 1982; Congdon et al. 1982; Nagy 1983; Pough et al. 1992; Nagy et al. 1999; McNab 2002; Suarez 2012). Putting it simply, every living organism requires energy to exist and the patterns of its acquisition and utilization are fundamental for the success of any given species.